2015
DOI: 10.1002/chem.201406539
|View full text |Cite|
|
Sign up to set email alerts
|

Randomizing the Unfolded State of Peptides (and Proteins) by Nearest Neighbor Interactions between Unlike Residues

Abstract: To explore the influence of nearest neighbors on conformational biases in unfolded peptides, we combined vibrational and 2D NMR spectroscopy to obtain the conformational distributions of selected "GxyG" host-guest peptides in aqueous solution: GDyG, GSyG, GxLG, GxVG, where x/y=A, K, L, V. Large changes of conformational propensities were observed due to nearest-neighbor interactions, at variance with the isolated pair hypothesis. We found that protonated aspartic acid and serine lose their above-the-average pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(83 citation statements)
references
References 99 publications
8
74
1
Order By: Relevance
“…However, over the last 15 years, experimental and computational studies have revealed that individual residues differ with regard to the conformational sampling, with the conformational entropy of short peptides and disordered and unfolded proteins being significantly less than assumed. [9][10][11][12][13][14][15][16][17] Recent results from MD and DFT computations have pointed to the same direction. [18][19][20][21][22][23][24] All residues predominantly sample the upper left quadrant of the Ramachandran plot, and they differ mostly in terms of their population of the polyproline II (pPII) (φ > -100 0 , ψ > 100 0 ) and β-strand region (φ ≤ -100 0 , ψ > 100 0 ).…”
Section: Introductionmentioning
confidence: 86%
“…However, over the last 15 years, experimental and computational studies have revealed that individual residues differ with regard to the conformational sampling, with the conformational entropy of short peptides and disordered and unfolded proteins being significantly less than assumed. [9][10][11][12][13][14][15][16][17] Recent results from MD and DFT computations have pointed to the same direction. [18][19][20][21][22][23][24] All residues predominantly sample the upper left quadrant of the Ramachandran plot, and they differ mostly in terms of their population of the polyproline II (pPII) (φ > -100 0 , ψ > 100 0 ) and β-strand region (φ ≤ -100 0 , ψ > 100 0 ).…”
Section: Introductionmentioning
confidence: 86%
“…However, it was clear that effects of neighboring residues are not negligible, and a calibration using the increasingly growing library of values recorded for highly disordered systems, which permits the effect of nearest neighbors to be taken into account, provides a better reference for values representative of complete disorder . In order to gain mechanistic insights into the relation between nearest neighbors and ϕ/ψ distributions, the distribution of a given amino acid may be compared to that of the residue embedded in a sequence of Gly residues . The impact of nearest neighbors on 3 J HN‐Hα values, relative to Gly‐embedded residues, correlates reasonably well with nearest neighbor effects measured in a series of blocked dipeptides, with small systematic differences attributed to the effect of the adjacent blocking groups .…”
Section: Introductionmentioning
confidence: 99%
“…2,5,7 The structure dependence of the delocalization of occupied orbitals invalidate Flory's isolated pair hypothesis, which are in line with experimental results. 23,24 The huge difference between the corresponding occupied MOs of GAG in implicit and explicit water strongly suggest that solvation energies of different residues are not additive.…”
mentioning
confidence: 99%